(untitled) (Research, Society and Development, 2020)
Onychomycosis are fungal infections of nails caused by pathogenic fungi, dermatophytes, non-dermatophytes and especially by species of the genus Candida. Yeast fungi cause infections in nails, due to their ability to invade the hyponychium, proximal border and by vascular or lymphatic dissemination, representing an important worldwide public health problem. In order to understand the low efficacy of treatment for onychomycosis and phenotypic changes caused by resistance mechanisms this study was to evaluate the susceptibility profile of onychomycosis clinical isolates of Candida to conventional antifungal. The antifungal sensitivity test for different strains and clinical isolates obtained from the Micoteca of the Laboratory of Antibacterial and Antifungal Activity of Natural and Synthetic Bioactive Products was carried out by the disk diffusion test. In view of the observed results, it can be inferred that the isolates had a high degree of resistance to azole drugs, considered to be drugs of first choice in the treatment of onychomycosis. Therefore, prior knowledge of in vitro tests can help in the pharmacotherapy of onychomycosis and monitoring prevalence of susceptibility profile to conventional antifungal and how perspective should use other susceptibility test to antifungal drugs and molecular techniques for a better understanding of phenotypes resistance.